A new canopy-dwelling species of Dendrelaphis (Serpentes: Colubridae) from Sinharaja, World Heritage Site, Sri Lanka - Wickramasinghe, L.j. Mendis (Zootaxa, 2016)
A new species of Dendrelaphis, Dendrelaphis sinharajensis sp. nov. is described, the sixth species of the genus known from Sri Lanka. The new species is readily distinguished from all other congeners by its colour pattern and scalation. The species is a canopy-dweller known only from the Sinharaja World Heritage Site and its vicinity, in the lowland wet zone of Sri Lanka.